2015
DOI: 10.1002/cphc.201500583
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Solvation Structure of l‐Leucine in Alcohol–Water Binary Solvents through Molecular Dynamics Simulations and FTIR and NMR Spectroscopy

Abstract: The solvation structures of l-leucine (Leu) in aliphatic-alcohol-water and fluorinated-alcohol-water solvents are elucidated for various alcohol contents by using molecular dynamics (MD) simulations and IR, and (1) H and (13) C NMR spectroscopy. The aliphatic alcohols included methanol, ethanol, and 2-propanol, whereas the fluorinated alcohols were 2,2,2-trifluoroethanol and 1,1,1,3,3,3-hexafluoro-2-propanol. The MD results show that the hydrophobic alkyl moiety of Leu is surrounded by the alkyl or fluoroalkyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 66 publications
3
14
0
Order By: Relevance
“…The specific interaction may act between the outside ethyl groups of TEA + and the TFE C–F bonds, such as the C–H···F–C weak hydrogen bonds. This weak hydrogen bond has been reported by many chemists. …”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The specific interaction may act between the outside ethyl groups of TEA + and the TFE C–F bonds, such as the C–H···F–C weak hydrogen bonds. This weak hydrogen bond has been reported by many chemists. …”
Section: Resultssupporting
confidence: 70%
“…However, the hydrogen-bond acceptability of the TFE oxygen atom is much lower than that of EtOH due to the electron drawal by the three fluorine atoms. In contrast, the trifluoromethyl group of TFE may interact with the hydrophobic alkyl chain of TEA + through the C–H···F–C weak hydrogen bonds, as reported in the literature. On the contrary, AN does not act as a hydrogen-bonding donor but acts as a hydrogen-bonding acceptor. The dipole moment (11.47 × 10 –30 C m) of AN is higher than those (5.67 × 10 –30 and 6.77 × 10 –30 C m, respectively) of EtOH and TFE .…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…That is, MeOH can tend to interact with water molecules, and IPA favors a hydrophobic environment compared with MeOH. In addition, Takamuku et al reported that the alcohol with a long alkyl chain showed effective interaction with the Leu alkyl chain in the order of IPA > EtOH > MeOH . These differences of physical properties of alcohol molecules having various alkyl chains suggested that IPA and EtOH may penetrate a hydrophobic layer of the peptide assembly more and deeper than MeOH and may therefore loosen the packing of amphiphilic peptides, resulting in a lower curvature and a larger diameter of the nanotube assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we studied the effect of a binary solvent on the hydration shell around each component of peptide S30L12 using the monomers Leu, Aib, and Sar in order to further understand the behavior of alcohols with S30L12. The nature of the interaction of the Leu side chain with different alcohols was understood by the simulation and IR experimental studies by Takamuku et al 62 IR spectra of the C−H stretching vibrational band of the Leu side chain in H 2 O with varying ratios of aliphatic alcohols (MeOH, EtOH, and IPA) indicated that the water molecule around the Leu alkyl chain was gradually decreased by increasing the alcohol content, which was evidenced by the red-shift in the IR spectra. Consequently, the length of the contracted Leu alkyl C−H bond in aqueous condition was recovered by the addition of aliphatic alcohol, indicating the reduction of the hydration shell in the alcohol/ H 2 O mixture.…”
Section: ■ Results and Discussionmentioning
confidence: 99%